Teknologi Kendali Kamera FPV 2 DOF Melalui Gesture Kepala Dengan Sensor IMU (Inertial Measurement Unit) - Suharizkiadi Suharizkiadi; Sony Matang (Nucleus Journal, 2024)
In taking videos or photos while in the air, there are currently very many tools or media that can be used and with the current technology that is very rapidly developing, especially in science, it can do everything easily. In the electronic field, a drone is a device that can fly and be controlled unmanned using a remote control. This object has a designation that is called a UAV (Unmanned Aerial Vehicle). This drone has a variety starting from the shape, size, different characters, and functions. FPV is one of the important parts of the 2DOF FPV (first person view) drone as a head gesture combined with parts such as nano arduino, Blueotooth HC-04, Servo, servo tilt up, IP camera, nano arduino must be connected to bluetooth on the cellphone, servo functions as moving right and left in accordance with the user's head gesture, servo tilt up functions as a gesture from top to bottom according to the gesture of the user and IP camera functions as video streaming, VR Glasses or commonly called Googles are connected using HC-04 bluetooth. According to the function in VR Glasses, it will bring up the sensitivity and movement value on the servo and servo tilt up and display the camera display on the IP camera.